2017
DOI: 10.1016/j.jand.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Mothers’ Views of the Fathers’ Role in Promoting Healthy Behaviors at Home: Focus Group Findings

Abstract: Background Overweight and obesity prevention interventions rarely take into account the unique role of fathers in promoting healthy home environments. Objective To use qualitative methodology to examine the views of Hispanic mothers of 2-to-5-year-old children regarding fathers’ roles in promoting healthy behaviors at home. Design Nine focus groups were conducted in Spanish with Hispanic mothers of preschool-aged children (n=55) from October to December, 2015. Participants/settings Hispanic mothers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 57 publications
6
53
0
2
Order By: Relevance
“…The current literature examining Latinos' parenting and their children's health-related behaviours focuses primarily on Latina mothers' beliefs, attitudes and practices related to their young children's eating, PA and SB (8,11,13,(14)(15)(16)(17)(18)(19)(20)(48)(49)(50)(51)(52) . To date, there is a paucity of information on these topics among Latino fathers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current literature examining Latinos' parenting and their children's health-related behaviours focuses primarily on Latina mothers' beliefs, attitudes and practices related to their young children's eating, PA and SB (8,11,13,(14)(15)(16)(17)(18)(19)(20)(48)(49)(50)(51)(52) . To date, there is a paucity of information on these topics among Latino fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, although the role of fathers in the promotion of their children's eating, PA and SB is a growing area of research, there is still limited information available on the role of minority fathers including Latinos (17,(36)(37)(38)(39)(40) . The current study provides insights into the role of Latino fathers in promoting their children's eating, PA and SB within the family environment and contributes information that allows for a more complete picture of how Latino parents view eating and PA environments for their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, grandparents are an important source of support in the UK, with over one-quarter of children < 5 years of age receiving care from grandparents [46]. Evidence suggests that fathers and grandparents offer larger portion sizes of less healthy foods to their children than mothers [12,47,48]; therefore, further investigation into the factors that influence fathers' and grandparents' portion size decisions may be beneficial for the development of tailored interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This may mean incorporating the entire family unit in a program or tailoring a program to incorporate specific family members. A recent study of Latina mothers found differences between mothers' and fathers' food parenting preferences and practices, therefore suggesting implications for nutrition education with Latino families (Lora, Cheney, & Branscum, 2017). Family-based programming may also include working with individuals to understand the influences of family systems through perceived roles, past family food experiences, and identifying influences of interactions between multiple subsystem members.…”
Section: Recommendations For Future Research and Practicementioning
confidence: 99%